The role of diabetes on the development of abdominal aortic aneurysms (AAA) - Siwek, Michal; Beutler, Jacek; Beutler, Katarzyna; Lewandowski, Jędrzej (Journal of Education, Health and Sport, 2024)
An abdominal aortic aneurysm (AAA) is a pathological local dilatation of the abdominal aorta that may develop from a variety of causes. With a 80% mortality rate, it is mainly linked to male gender, age above 65 years, smoking, and a family history of AAA. Ultrasonography is an effective method for screening males who are 65 or older for AAA. Endovascular aneurysm repair (EVAR) procedure reduces 30-day operative mortality and hospital stay, becoming a global standard. Both open and endovascular surgery aim to cut off the aneurysm’s circulation, preventing it from rupturing. Diabetes mellitus (DM) may provide protection against regrowth and the need for additional intervention after endovascular AAA repair, thereby limiting the enlargement and rupture of AAAs. Hyperglycemia thickens the aortic walls and reduces wall stress in diabetic patients’ abdominal aortas. It stabilizes collagen structure and promotes the synthesis of collagen type IV. Anti-diabetic drugs like metformin, thiazolidinedione, and dipeptidyl peptidase 4 inhibitors (DPP-4i) have been shown in both animal and human studies to protect against aortic aneurysms. In a dose-response pattern, these antidiabetic drugs may lower the prevalence, incidence, and enlargement rate of AAA.